Long Intergenic Noncoding RNAs Mediate the Human Chondrocyte Inflammatory Response and Are Differentially Expressed in Osteoarthritis Cartilage. Issue 4 (April 2016) - Pearson, Mark J.; Philp, Ashleigh M.; Heward, James A.; Roux, Benoit T.; Walsh, David A.; Davis, Edward T.; Lindsay, Mark A.; Jones, Simon W.
Abstract : Objective: To identify long noncoding RNAs (lncRNAs), including long intergenic noncoding RNAs (lincRNAs), antisense RNAs, and pseudogenes, associated with the inflammatory response in human primary osteoarthritis (OA) chondrocytes and to explore their expression and function in OA. Methods: OA cartilage was obtained from patients with hip or knee OA following joint replacement surgery. Non‐OA cartilage was obtained from postmortem donors and patients with fracture of the neck of the femur. Primary OA chondrocytes were isolated by collagenase digestion. LncRNA expression analysis was performed by RNA sequencing (RNAseq) and quantitative reverse transcriptase–polymerase chain reaction. Modulation of lncRNA chondrocyte expression was achieved using LNA longRNA GapmeRs (Exiqon). Cytokine production was measured with Luminex. Results: RNAseq identified 983 lncRNAs in primary human hip OA chondrocytes, 183 of which had not previously been identified. Following interleukin‐1β (IL‐1β) stimulation, we identified 125 lincRNAs that were differentially expressed. The lincRNA p50‐associated cyclooxygenase 2–extragenic RNA (PACER) and 2 novel chondrocyte inflammation–associated lincRNAs (CILinc01 and CILinc02) were differentially expressed in both knee and hip OA cartilage compared to non‐OA cartilage. In primary OA chondrocytes, these lincRNAs were rapidly and transiently induced in response to multiple proinflammatory cytokines. Knockdown of CILinc01 and CILinc02 expression in human chondrocytes significantly enhanced the IL‐1–stimulated secretion of proinflammatory cytokines. Conclusion: The inflammatory response in human OA chondrocytes is associated with widespread changes in the profile of lncRNAs, including PACER, CILinc01, and CILinc02. Differential expression of CILinc01 and CIinc02 in hip and knee OA cartilage, and their role in modulating cytokine production during the chondrocyte inflammatory response, suggest that they may play an important role in mediating inflammation‐driven cartilage degeneration in OA.